Strengthening the Values of Religious Moderation in Majlis Ta’lim Al Karomah Sempu Pasir Gombong, Cikarang Utara, Bekasi - Karyoto; Sudarma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The strengthening of religious moderation values in the context of Majelis Ta'lim has become highly relevant in addressing social challenges and diversity in Indonesia. As an informal religious educational institution that has rapidly developed, Majelis Ta'lim plays a crucial role in shaping moderate religious understanding, characterized by an inclusive, tolerant, and balanced approach to religious practice. This study aims to understand the role of Majelis Ta'lim in teaching religious moderation values and its impact on fostering tolerance and openness to differences. The research method used is a qualitative approach with interview, observation, and document analysis techniques. Data collection techniques involve documentation from various relevant sources. Data analysis is conducted using an inductive approach to identify key themes related to the implementation of religious moderation in Majelis Ta'lim. The findings indicate that Majelis Ta'lim plays a role in teaching moderation values through sermons, discussions, and religious teachings that promote mutual respect among religious communities. Strengthening religious moderation in Majelis Ta'lim can cultivate tolerance, openness, and awareness of the importance of living harmoniously in diversity.